If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(4x + 2) = -56 Reorder the terms: 4(2 + 4x) = -56 (2 * 4 + 4x * 4) = -56 (8 + 16x) = -56 Solving 8 + 16x = -56 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 16x = -56 + -8 Combine like terms: 8 + -8 = 0 0 + 16x = -56 + -8 16x = -56 + -8 Combine like terms: -56 + -8 = -64 16x = -64 Divide each side by '16'. x = -4 Simplifying x = -4
| [3x-2]+3=7 | | Y=6.5x+145 | | 7+2x-4x=-10+5 | | 8x+4y=2fory | | 8(2x+3)=10(x-3) | | 8(2x+3)=10x-3 | | 3k^2+7k=0 | | 15x+8-1=3x+5 | | 2x+5y-z=5 | | 3x+6-4x-3=6 | | 15v*3-170v^2+400v=0 | | 3+5x+2-2x=-5+6x+7-4x | | 8(w+8)=8w+16 | | 3x+x-8=3x+5 | | 2(3x-4)-6(x+1)=-x+4(x+10) | | 1.5(4.5+.9y)-1.9y=-29 | | 3=-1/3x | | x^2+18=50 | | 4(g+5)=8 | | 2x+3x=5(y-3)+23 | | 4x^3+18x^2-12x-52=0 | | 38.72+0.25m=100 | | (x+2)(x-5)(x-(3+2i))(x-(3-2i))=0 | | 23x-24x+2x=8x-7+2 | | X*25+.45=X*40+.25 | | -3x-5=6x+22 | | -2n+4(3-n)=2(4n+34) | | (x+30)/20=(2/4)x | | r+14=26 | | (x+30)/20=2/4x | | 9y+(-4x)-8x+1-5y+5= | | 5X+2Y=4Y |